Late Awakening Is Common in Settings Without Withdrawal of Life-Sustaining Therapy in Out-of-Hospital Cardiac Arrest Survivors Who Undergo Targeted Temperature Management*. Issue 2 (February 2022) - Lee, Dong Hun; Cho, Yong Soo; Lee, Byung Kook; Lee, Hyoung Youn; Jeung, Kyung Woon; Jung, Yong Hun; Park, Kyu Nam; Kim, Youn-Jung; Chae, Minjung Kathy; Seo, Dong-Woo
Abstract : OBJECTIVES: We investigated awakening time and characteristics of awakening compared nonawakening and factors contributing to poor neurologic outcomes in out-of-hospital cardiac arrest survivors in no withdrawal of life-sustaining therapy settings. DESIGN: Retrospective analysis of the Korean Hypothermia Network Pro registry. SETTING: Multicenter ICU. PATIENTS: Adult (≥ 18 yr) comatose out-of-hospital cardiac arrest survivors who underwent targeted temperature management at 33–36°C between October 2015 and December 2018. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: We measured the time from the end of rewarming to awakening, defined as a total Glasgow Coma Scale score greater than or equal to 9 or Glasgow Coma Scale motor score equals to 6. The primary outcome was awakening time. The secondary outcome was 6-month neurologic outcomes (poor outcome: Cerebral Performance Category 3–5). Among 1, 145 out-of-hospital cardiac arrest survivors, 477 patients (41.7%) regained consciousness 30 hours (6–71 hr) later, and 116 patients (24.3%) awakened late (72 hr after the end of rewarming). Young age, witnessed arrest, shockable rhythm, cardiac etiology, shorter time to return of spontaneous circulation, lower serum lactate level, absence of seizures, and multisedative requirement were associated with awakening. Of the 477 who woke up, 74 (15.5%) had poor neurologic outcomes. Older age, liver cirrhosis, nonshockable rhythm, noncardiac etiology, a higher Sequential Organ Failure Assessment score, and higher serum lactate levels were associated with poor neurologic outcomes. Late awakeners were more common in the poor than in the good neurologic outcome group (38/74 [51.4%] vs 78/403 [19.4%]; p < 0.001). The awakening time (odds ratio, 1.005; 95% CIs, 1.003–1.008) and late awakening (odds ratio, 3.194; 95% CIs, 1.776–5.746) were independently associated with poor neurologic outcomes. CONCLUSIONS: Late awakening after out-of-hospital cardiac arrest was common in no withdrawal of life-sustaining therapy settings and the probability of awakening decreased over time. Abstract : Supplemental Digital Content is available in the text.